Metastasis of Melanoma to the Adrenal Glands: A Case Report and Literature Review - Haider, Asad A; Ruiz de Villa, Ariel; Frimer, Leora; Bazikian, Yvette (Curēus (Palo Alto, CA), 2022)
Immune checkpoint inhibitors have significantly improved the prognosis of metastatic melanoma, but metastases to the adrenal glands remain highly resistant to these new treatments. Adrenal gland metastases from melanoma can present in an unusual manner, such as in this report, making it diagnostically and therapeutically challenging. In this case report, we present a patient with histologically confirmed metastatic melanoma to the adrenal glands, a large intracardiac mass suspicious for metastatic disease, and an inferior vena cava thrombus. We review the existing literature to explain the unique characteristics, clinical relevance, pathogenesis, diagnosis, and treatment of adrenal gland metastases from melanoma.